2023
DOI: 10.4102/sajp.v79i1.1851
|View full text |Cite
|
Sign up to set email alerts
|

South African physiotherapists’ attitudes to medicine prescription as an extension of practice

Tsungirirai V. Kakono,
Desmond Mathye,
Sarel J. Brand
et al.

Abstract: Background: The extension of medicine prescription rights to other healthcare providers was proposed to reduce pharmacotherapeutic service delivery challenges in the South African healthcare sector. The scope of practice of physiotherapists is being reviewed to possibly include prescription rights to promote service delivery.Objectives: Our study assessed the attitudes of registered South African physiotherapists to the inclusion of prescription rights in their scope of practice, including enablers and challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 38 A South African study conducted in 2023 revealed that most physiotherapists support the inclusion of prescribing rights in their scope of practice and were aware of the required educational training. 39 …”
Section: Discussionmentioning
confidence: 99%
“… 38 A South African study conducted in 2023 revealed that most physiotherapists support the inclusion of prescribing rights in their scope of practice and were aware of the required educational training. 39 …”
Section: Discussionmentioning
confidence: 99%